Indeks Subjek Volume 27, Tahun 2007 - Indeks Subjek Volume 27, Tahun 2007 (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2007)
AHP 48Amylose content 112Antibacterial activity 7,89Antioxidant 70,107,147Antioxidative activity 18Artificial neural network 75Biduri protease 100Biomicro 137Canarium 165Chemical composition 1Coastal sandy soil 137Cocoa 18Commad area 182Comsumption pattern 33Copper 158Cotton 176Creamed latex 124Customer service level 41Deep-fat frying 27Delinter enginering176DPPH 70,107,147Dry fractionation 171DSC 171Effervescent tablet 70Egg protein 7Encapsulation 118Fat uptake 27Fatty acids 165Fermentation 12Flavor 118Food budget 33Fuzzy set theory 59Gambir 89Gasification 130Gelatinization 112Gelling agents 1Goat meat 1Germination 152Heat 130Heating 7Image processing 75Immobilized metal ions 158Iron 7Irrigation 137rigation infrastructureI 182Irrigation operation 48Irrigation performance 59Lactic acid bacteria 12Linoleic-thiocyanate 107